Safe at home?: policing the U.S. hometown in a post 9/11 environment - Kerlikowske, R. Gil (Crime, law and social change, 2008)
Despite the prominence of terrorism concerns on the national agenda, three areas of public policy pose more significant challenges for local law enforcement in the United States: illegal gun proliferation and distribution; offender incarceration and re-entry paths; and investments in the lives of children. This paper argues that the current direction of public policy in these latter areas should be a primary concern, because these policies not only impact law enforcement in a negative way, but also threaten the strength and vitality of the communities law enforcement is trying to serve. Moreover, the dangers posed by these policies are far more calculable, more likely and more destructive over the long run than those posited for more extreme, though less-likely threats, to which the U.S., as a nation, is committing enormous sums of money, for seemingly incremental, public safety benefits. The role of law enforcement executives is critical to how these issues will be addressed.